2019
DOI: 10.1080/23144599.2019.1637046
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenic and host range determinants of reassortant Egyptian low pathogenic avian influenza H9N2 viruses from backyard chicken

Abstract: Since the introduction of H9N2 low pathogenic avian influenza virus in Egypt, it became an endemic disease causing considerable economic losses in different poultry sectors especially in the presence of other secondary bacterial and viral infections. The H9N2 viruses in Egypt are in continuous evolution that needs deep analysis for their evolution pattern based on the genetic constitutions of the pathogenic determinant genes (HA, PB2, PB1, PA, and NS). In this work, samples were collected from the backyard chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The endemicity and widespread of H9N2 AIV infection among the poultry population in Egypt have made it an additional risk factor in the poultry industry. H9N2 AIV also has the potential to be transmitted to humans, especially with the cocirculation of other influenza subtypes in Egypt [ 18 , 24 ]. Available epidemiological data revealed that H9N2 AIV was initially distributed through Lower Egypt and Giza Governorate.…”
Section: Discussionmentioning
confidence: 99%
“…The endemicity and widespread of H9N2 AIV infection among the poultry population in Egypt have made it an additional risk factor in the poultry industry. H9N2 AIV also has the potential to be transmitted to humans, especially with the cocirculation of other influenza subtypes in Egypt [ 18 , 24 ]. Available epidemiological data revealed that H9N2 AIV was initially distributed through Lower Egypt and Giza Governorate.…”
Section: Discussionmentioning
confidence: 99%
“…H9N2 virus target protein data were acquired from online databases, including the Protein Data Bank (https://www.rcsb.org/ (accessed on 1 April 2021)) and The European Bioinformatics Institute (https://www.ebi.ac.uk/ (accessed on 1 April 2021)). From this collection, we identified five significant proteins of the H9N2 virus, including polymerase basic protein2 (PB2), polymerase basic protein1 (PB1), polymerase acidic protein (PA), hemagglutinin (HA), and neuraminidase (NS) [28], which are targets of the active compounds that inhibit the avian influenza A/H9N2 virus [29]. Because the aforementioned five proteins were confirmed to be significant targets of the H9N2 virus [28], this study focuses on finding significant compounds in these five proteins.…”
Section: Data Collection and Selectionmentioning
confidence: 99%
“…In 2014, a reassortant LPAIV H9N2 was reported in pigeon containing five internal gene segments (PB2, PB1, PA, NP, and NS) form Eurasian AIV subtypes (Kandeil et al, 2017). The same genotype was found in backyard chickens in three Egyptian governorates in 2015 (Samir et al, 2019). Recently a new genotype was described similar to the reassortant H9N2 but inherited its NP gene segment from the Egyptian 2010 H9N2 viruses (Kandeil et al, 2019).…”
Section: Introductionmentioning
confidence: 97%